1988
DOI: 10.1007/bf00033425
|View full text |Cite
|
Sign up to set email alerts
|

Phytosociology and ecology of old hay meadows in Hordaland, western Norway in relation to management

Abstract: Well-drained mown hay meadows in Hordaland, western Norway, were investigated. The hay meadows are either managed in a traditional or in a semi-traditional way. Traditional management in the area involves little or no use of manure or fertilizer, mowing once or twice a year with a first cut later than June 23, clearing in spring and intensive grazing for short periods in spring and autumn. Semi-traditional management involves use of small to medium quantities of commercial fertilizer, often in addition to manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 37 publications
(23 reference statements)
1
31
0
2
Order By: Relevance
“…Due to changes in the traditional land-use related to agriculture, many areas have been converted to arable land or tree plantations and others have been fertilised (e.g. Losvik 1988, Bengtsson-Lindsj6 et al 1991, Ihse 1995. Apart from being suitable targets for studies of Table 2.…”
mentioning
confidence: 98%
“…Due to changes in the traditional land-use related to agriculture, many areas have been converted to arable land or tree plantations and others have been fertilised (e.g. Losvik 1988, Bengtsson-Lindsj6 et al 1991, Ihse 1995. Apart from being suitable targets for studies of Table 2.…”
mentioning
confidence: 98%
“…Mowing early in the season favors late flowering plants without rosettes (Losvik, 1988) and in fact, in the second year, we found that E. californica* had 6.7 plants per square meter in the early season mowed plots versus 3.3 and 1.7 plants per square meter in the mid and in the late-season mowed plots, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…Lateseason mowing not only enabled the species to produce seeds, but presumably also enabled the perennials to allocate nutrients to below-ground reserves (Huhta, Rautio, Tuomi, & Laine, 2001). A late cut in fact enables the seeds to ripen and creates light for the species in lower field layers (Losvik, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The mean temperature in January is 0.58C, and the mean annual temperature is 7.28C (Aune 1993). The soil is rich in minerals (base saturation: 54 Á76%), and poor in organic matter (carbon: 2.3 Á3.8%, nitrogen: 0.31 Á0.47%, and phosphorus: 0.2 Á0.5mg/100 g dry matter), while the pH varies between 5.1 and 5.6 (Losvik 1988).…”
Section: Study Areamentioning
confidence: 99%